Financialization made in Germany: A review - Daniel Detzer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
This article examines the spread of financialization in Germany before the financial crisis. It provides an up-to date overview on the literature on financialization and reviews which of the phenomena typically associated with financialization have emerged in Germany. In particular, the article aims to clarify how the prevailing institutional structure and its changes had contributed to or had countervailed the spread of financialization and how it had shaped the specific German variant of financialization. For this end, it combines the rich literature on Germany's institutional structure with the more macroeconomic oriented literature on financializaton. With the combination of those different perspectives the article sheds light on the reasons for the spread of financialization and the specific forms it has taken in Germany.
Keywords: E44; F40; G20; G30; K22; 330; Banking; Corporate Governance; Financialization; Financial Sector; Financial Regulation; Varieties of Capitalism